Qing-Re-Hua-Shi Decoction ameliorates DSS-induced colitis by modulating multiple signaling pathways and remodeling the gut microbiota and metabolite profile - Chen, Wei; Xu, Lin; Wang, Long; Shan, Yu-nan; Li, Yan; Zhu, Jin-shui (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundClinically, Qing-Re-Hua-Shi Decoction (QRHSD) has been clinically used to treat ulcerative colitis (UC) with satisfactory outcomes and minimal side effects. However, its molecular mechanisms remain unclear.PurposeThis study investigates the effects of QRHSD on DSS-induced colitis in mice, employing multi-omics analyses, including RNA-seq transcriptomics, 16S rRNA microbiomics, non-targeted metabolomics, and network pharmacology analysis.MethodsThe chemical composition of QRHSD was analyzed using quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). A UC mice model was induced by 3% DSS for 7 days. The effects and mechanisms of QRHSD on UC were evaluated via hematoxylin and eosin, immunofluorescence assay, flow cytometry, western blot, RNA-seq transcriptomics, 16S rRNA microbiomics, non-targeted metabolomics, and network pharmacology. Correlation analyses and validation experiments explored links between transcriptomic, microbiome, metabolomic profiles, and UC-related clinical indices.ResultsUPLC-Q-TOF/MS identified 55 compounds in QRHSD. QRHSD significantly reduced clinical activity, histological changes, and inflammatory factors in UC mice, regulated Th17/Treg balance, and enhanced intestinal barrier integrity. 16S rRNA analysis showed that QRHSD altered gut microbiota composition, increasing beneficial bacteria (e.g., Lactobacillus) and decreasing harmful bacteria (e.g., Morganella). Non-targeted metabolomics revealed 507 metabolites associated with UC amelioration, enriched in pathways like bile secretion, ABC transporters, and amino acid biosynthesis. RNA-seq analysis, network pharmacology, and experimental verification showed that QRHSD significantly regulated key signaling pathways, including PI3K/AKT, NF-κB, and MAPK signaling pathways. Finally, correlation analysis highlighted connections among UC-related clinical factors, gut microbiota, and metabolites.ConclusionQRHSD could modulate the gut microbiota, metabolic homeostasis, and multiple signal pathways in the treatment of DSS-induced UC, revealing the mechanism of traditional Chinese medicine therapy for UC.